Updating the Diagnosis and Management of Dementia. Practical Contributions in our Context - Ángel Julio Romero Cabrera; Eduardo Fernández Casteleiro; Julio López Argüelles; Julio Daniel Suz Piña; Juan Rafael Cordero Jiménez (Universidad de las Ciencias Médicas de Cienfuegos, 2012)
Considering as our main goal to expose the state of the art in diagnosis and treatment of dementia insisting in its latest advances and suggesting practical contributions for its management in our context, we offer a panoramical view of dementia as an important health problem and expose the essentials for its diagnosis and management including cognitive impairment diagnosis, variants, etiologic diagnosis, the diagnosis of demential syndrome, the importance of neuropsychiatric assessment and the treatment options. We emphasize in the need to provide appropriate orientation to families and those who take care of the elderly.